A Framework for Addressing the Twin Challenges of COVID-19 and Climate Change for Sustainable Agriculture and Food Security in South Asia - Rasul, Golam (Frontiers in Sustainable Food Systems, 2021)
Climate change has begun to ravage agriculture and threaten food security in many parts of the world. The novel coronavirus pandemic (COVID-19) has further disrupted agricultural activities and supply chains and has become a serious threat for public health. Like in many developing countries, South Asian farmers are now facing the double challenge of addressing the impacts of a changing climate and managing the disruptions caused by COVID-19. Despite growing concern, there is limited understanding of how climate change, public health, and COVID-19 interact, and of the possible pathways to achieving a climate-friendly recovery from COVID-19 to achieve food and nutrition security. In view of this, this paper explores the multifaceted challenges that farmers are now facing in South Asia due to climate change and the disruption caused by COVID-19 from the agricultural and food security lens. The analysis reveals that the complex interactions of COVID-19 and climate change have impacted all dimensions of food security. These interlinkages demand an integrated approach in dealing with food, public health, and climate change to harness synergies and minimize trade-offs between food production, public health, and climate mitigation. I present a framework to address the immediate challenge of COVID-19 and the longer-term challenge of anthropogenic climate change. Key elements of the framework include the strengthening health sector response capacities, strengthening of local and regional food systems, making agriculture resilient to pandemics, adopting flexible and smart approaches—including the implementation of climate-smart agricultural interventions on different scales, promotion of appropriate research and innovation, and the integration of short-term support to address the challenges of COVID-19 to build long-term productivity, and resilience of food systems by investing on natural capital. This framework would enable policy makers to choose the appropriate policy responses at different scales, to address these twin challenges of COVID-19 and climate change.